Identity construction among L2 writers in an Egyptian university - Abousaeed, Duaa Zein (AUC Knowledge Fountain, 2020)
The purpose of this study is to explore how students in an undergraduate language program represent their identities in L2 writing. The study investigates the effects of gender on ways of constructing identities in L2 writing and examines the relationship between overall L2 writing quality, identity features using both qualitative and quantitative research. A convenience sample of two English teaching Egyptian professors and 115 randomly-selected Egyptian male and female students in a public university participate in this study. Interviews with two professors who have different years of teaching experience are administered. The researcher also assigned students a writing task to identify different ways males’ and female’ constructed identities related to their writing quality. A combination of T-test and correlational analyses were conducted to analyze the effect of gender on identity features and to examine the relationship between identity features and overall writing quality. Hyland’s model of metadiscourse in academic texts was used as a basis for this study (2005), in addition to a ‘reader-based’ approach, suggested by Matsuda and Tardy (2007). To meet the requirement for the ‘reader-based’ approach, this study necessitated adjusting the ‘Voice Intensity Rating Scale’ (AVIRS) of Helms-Park and Stapleton (2003). The writing samples were scored by two raters using the (AVIRS) for scaling identity and a TOEFL iBT Holistic rubric for grading the overall L2 writing quality. The analyses of the results showed that undergraduates adopted ‘self-identification’, ‘assertiveness’ and ‘authorial presence’ to demonstrate their writing identities. The results also demonstrated that gender had no effect on ways of constructing identities in L2 writing. The findings yielded a positive significant correlation between ‘engagement markers’ and the overall L2 writing quality; in addition to three positive correlations between ‘authorial presence’, ‘central point’, ‘total identity feature’, and the writing quality in males and females respectively. The results confirm that intensity of identity features raises the overall L2 writing quality for both males and females.